1987
DOI: 10.1111/j.1476-5381.1987.tb11291.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of single and repeated electroconvulsive shock administration on the release of 5‐hydroxytryptamine and noradrenaline from cortical slices of rat brain

Abstract: 1 A method is described ofmeasuring the K+-evoked release ofendogenous 5-hydroxytryptamine (5-HT) and noradrenaline (NA) from slices prepared from rat cortex. 2 There was no difference in either the spontaneous (basal) or K+-evoked release of 5-HT or NA from cortical slices prepared from handled animals and those given a single electroconvulsive shock (ECS) either 30 min or 24 h earlier.3 In chronic studies, rats were either handled or given an ECS 5 times over 10 days and cortical slices prepared. There was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…However, the pattern of regional changes in interstitial monoamine concentrations induced by acute ECS (Glue et al, 1990) parallels that of TMS. r-TMS had no effect on NE levels, which is in agreement with previous findings on ECS effects in whole brain and slices from frontal cortex (Nimgaonkar et al, 1986;Green et al, 1987).…”
Section: Discussionsupporting
confidence: 94%
“…However, the pattern of regional changes in interstitial monoamine concentrations induced by acute ECS (Glue et al, 1990) parallels that of TMS. r-TMS had no effect on NE levels, which is in agreement with previous findings on ECS effects in whole brain and slices from frontal cortex (Nimgaonkar et al, 1986;Green et al, 1987).…”
Section: Discussionsupporting
confidence: 94%
“…These findings argue that the noradrenaline reuptake inhibitor, desipramine, probably causes adaption by increasing the synaptic concentrations of this neurotransmitter. By contrast, ECS almost certainly produces this effect by an indirect, but as yet, undefined mechanism and this hypothesis is supported by earlier studies showing that ECS has little effect on noradrenaline turnover or release (Nimgaonkar et al, 1986;Green et al, 1987). This finding of a differential necessity for an intact noradrenergic input in the attenuation of postsynaptic a2-adrenoceptors by desipramine and ECS mirrors the previously reported requirements for the down-regulation of fl-adrenoceptors by these two antidepressant treatments, i.e.…”
Section: Discussionsupporting
confidence: 79%
“…ECS has been reported to alter central nervous system functions. A decrease in acetylcholine (ACh) levels (Spignoli and Pepeu, 1986) and an increase in acetylcholinesterase activity (Appleyard et al, 1987), inhibition of GABA synthesis and increase in noradrenaline and serotonin release (Green et al, 1987a(Green et al, , 1987b have been reported.…”
Section: Discussionmentioning
confidence: 99%